The Therapeutic Effect and Potential Pharmacological Mechanisms of Ding-Zhi-Xiao-Wan on Depression were Investigated by Meta-analysis, Network Pharmacology and Molecular Docking - Lin, Li-Li; Wu, Han-Biao; Qiu, Zhi-Kun (Current Computer - Aided Drug Design, 2024)
Introduction Ding-Zhi-Xiao-Wan (DZXW) produces potential antidepressant-like effects. However, its antidepressant mechanisms are still unclear. Objective To analyze the antidepressant effects and the pharmacological mechanisms of DZXW, meta-analysis, network pharmacology, and molecular docking were selected in this study. Methods The compounds of DZXW and genes associated with compounds or depression were obtained from databases. The genes overlapping between DZXW compounds and depression were compared by Venn diagram. A network of medicine-ingredients-targets-disease was constructed, visualized, and analyzed. Protein-protein interaction, gene ontology, pathway enrichment, and molecular docking were performed to evaluate the potential mechanisms of DZXW for the treatment of depression. Results Meta-analysis showed that the antidepressant-like effects were produced by DZXW. The network pharmacology analysis showed that a total of 74 compound-related genes and 12607 PTSD-related genes were identified in the databases with 65 overlapping genes. The active ingredients derived from DZXW (i.e Beta-sitosterol, Stigmasterol, Fumarine, Hederagenin) elicited the antidepressant-like effects by targets, such as ACHE, HTR2A, and CHRM1. Moreover, the signaling pathways, like neuroactive ligand-receptor interaction, pathways in cancer, and cholinergic synapse, might play important roles in the treatment of depression by DZXW. Conclusion This study provides studies analysis and molecular evidence with the beneficial effects of DZXW for the treatment of depression.
Keywords: depression